A study of the Chinese position on the Syrian crisis 2011-2018 - Mussa, Ouassfi (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to clarify that the modern Chinese state is based on the principle of non-interference in the foreign affairs of countries. Therefore, we find that a large group of those interested in Chinese affairs are most surprised by China’s use of the veto in the Security Council in the Syrian crisis twice within four months, knowing that it did not use it. Only eleven times over the course of more than forty years, this transformation confirms that there are great motives that pushed the Chinese regime to that, on top of which were economic motives, as China was afraid of besieging its traditional partners such as Iran, which is considered its most important supplier of oil and gas. This is in addition to the security factor and the danger it poses to Chinese security, especially if we know that the number of Chinese Uyghurs in Syria exceeds thousands.